PENGARUH LATIHAN SENAM AEROBIK TERHADAP PENURUNAN BERAT BADAN PADA PESERTA SANGGAR SENAM KIRAN PEKANBARU - Juliana BR Silalahi; Zainur Zainur; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The problem in this research is that there are 10 participants in the exercise who are overweight (obese). the fact that was received from the gymnastics participants led to an overweight that led to disease susceptibility and a lack of self-confidence. This type of research is an experiment with the One-Group Pretest-Posttest Design approach. The purpose of this research was to determine the effect of aerobic exercise on weight loss in gymnastics. The population in this research consisted of 10 participants from Kiran Pekanbaru gymnastics studio. The sampling technique used was targeted sampling, in which samples were taken according to certain criteria. The data collection technique was obtained from the pre-test and the post-test. The instrument in this research used the antrophometrik test as an aid to measure nutritional status. Pre-test results data after the LoMax calculation is 0.168 and the Ltable is 0.258. It can be concluded that the distribution of data from the antrophometrik results prior to the test is normally distributed. For the post-test test, the LoMax is 0.173 and the Ltable is 0.258. This means that LoMax is smaller than LTable. It can be concluded that the distribution of data from the post-test results is normally distributed. Analysis of the tcount between the initial test and the final test, the number is 3,330 and compared to the t-table value at a significant level of 0.05 degrees of freedom N - 1 (9) turns out to be 1,833, indicating that the tcount (3.330)> ttable (1.833), it can be concluded that the hypothesis that states that there is an effect of aerobic training on weight loss in participants of the Kiran gymnastics studio Pekanbaru.Key Words: Aerobic Exercise, Weight Loss